(untitled) (Feni University Journal, 2026)
Concrete is widely used for the construction of most buildings, bridges, and other structures throughout the world. The entire construction sector is currently looking for a suitable and usable unused product that would significantly reduce the consumption of fine aggregate and finally lower the cost of production. Pozzolanic materials like crushed brick powder can be used as a substitute for fine aggregate in mortar. In this study, crushed brick powder was used in proportion with fine aggregate, i.e., sand. Sand was replaced by crushed brick powder by percentage weight of sand up to 30% in 5% intervals. The compressive strength with 0% crushed brick powder was found to be 2661 psi, but as the percentage of crushed brick powder increased, the compressive strength also increased. The maximum compressive strength of 3597 psi was observed when 10% crushed brick powder was used. The compressive strength starts to decline after 10% of crushed brick powder. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (177-186)